“On the ways of Maqom (Suite) and the Rhythms in Folk Music” - Rasulov Marufjon Mamirjon ogli (Researchparks Publishing, 2021)
This article discusses the system of methods of the Uzbek classical music heritage, mainly individual and partial grouping, and analyzes the role and function of the popular rhythms in maqoms (suites).